A graph-based cost model for supply chain reconfiguration. (July 2018) - Guo, Weihong; Tian, Qi; Jiang, Zhengqian; Wang, Hui
Abstract: The emergence and growth of globalization require manufacturing enterprises to reconfigure their manufacturing systems and supply chains quickly and cost-effectively in response to market changes. In this paper, a supply chain reconfiguration problem for manufacturing enterprise systems was investigated. An optimization model was formulated to minimize the total cost of the supply chain network with the consideration of manufacturing operations and reconfiguration cost. To effectively model the reconfiguration cost of the supply chain, a graph-based method was proposed to characterize the similarity between supply chain configurations and to establish the relationship between the similarity index and reconfiguration cost. A case study on a supply chain for laptop computer manufacturing was presented to illustrate the proposed method and demonstrate its effectiveness.